Perbaikan Warehouse Finished Goods untuk Meningkatkan Level SMART Site Classification pada PT. SMART, Tbk - Christopher Kevin Purnomo; Herri Christian Palit; Karina Agustin (Jurnal Titra, 2020)
PT. SMART, Tbk is a company that produces palm oil. PT. SMART, Tbk has a finished goods warehouse, where the warehouse stores goods that have been purchased for distribution to consumers. In managing these products a good system in needed. The warehouse currently has a WMS (Warehouse Management System) system for warehousing in and out of the warehouse. In the context of ongoing improvement, the warehouse wants to increase the level of the SMART Site Classification which previously the warehouse gets one star from three stars. It is necessary to do in advance the SMART Site Classification to determine the initial conditions of the warehouse. The results of the initial review, which are used as a reference to make improvements, before making repairs must determine the priority scale value compared to daily warehouse operations. After improvement efforts were made, the point of the SMART Site Classification Level of PT. SMART increased from 74 points to 80 points.